Andragogy in nursing: a literature review - Patrícia Bover Draganov; Andréia de Carvalho Andrade; Vanessa Ribeiro Neves; Maria Cristina Sanna (Investigación y Educación en Enfermería, 2013)
Objective. To describe the use of the term andragogy in the contents of nursing publications. Methodology. Bibliographic study. A search was undertaken in the databases MEDLINE, LILACS, BDENF, EMBASE and ERIC, for articles published between 1999 and 2011 which included the term 'andragogy' or derived terms in the English language. Results. 51 publications were found. The study's main categories were: ideological and theoretical bases (71%), historical antecedents (37%), andragogy's operationalization (43%) and application in Nursing (86%). The most-frequently treated issue was continuing education (45%). Most articles were published in the United States (41%). In Brazil, the use of andragogy is more recent than in other countries. The studies indicate that andragogy has a positive influence in the students' work lives. Conclusion. Although the use of andragogy in nursing education is less frequent, its use in nurse training shows it to be important for future professional performance.